TANGGUNG JAWAB MEDIA CETAK DALAM MEMUAT BERITA YANG SALAH DI PT.RIAUPOS PEKANBARU PERSPEKTIF HUKUM PERDATA - Bella Nabila; Firdaus '; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Mass media is the delivery of information and communications delivered through intermediaries (media) to the general public. Mass media that is now used by the public form more diverse, one of which is the print media. In the civilization of mankind, newspapers are the oldest print mass media. A newspaper is a printed medium that contains news published every day. Newspapers are always required to reveal the truth of the news in fairness. In addition to fair reporting demands, newspapers are also required to do accurate news, which should not lie. Newspapers should always develop objective news. The information must also be balanced and fair in order that the published news does not harm the other side. But in fact, journalists could have stumbled over a case of misinformation and then it would cause harm to others. If any party feels aggrieved then a lawsuit can be executed. Therefore it is necessary to demand the responsibility of the media where the journalist works. The problems that will be discussed in this thesis is how the form of accountability of print media when loading the wrong news in the perspective of civil law.This type of research is sociological, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted at PT. Riau Pos Pekanbaru, while the population and the sample is the whole party related to the problem studied in this research, data source used, primary data, secondary data and tertiary data, data collection techniques in this study with interviews, questionnaires and literature study.From the result of the research, it can be concluded that based on Article 1365 of the Civil Code, those who feel disadvantaged over the wrong report are entitled to accountability. The print media shall perform its duty to be responsible for correcting or corrupting any wrong reporting in accordance with Article 1 Sub-Article 13 of the Correction Duty. The form of media accountability in the perspective of civil law is through the use of the right of reply or clarification of the news, through press councils, through courts or indemnities, and boycotting press companies.Keywords: Responsibility - Mass Media - Newspaper - Wrong News